Publisher Correction: Chitosan nanoparticles functionalized with β-cyclodextrin: A promising carrier for botanical pesticides publisher - Campos, Estefânia V. R. [UNESP]; Proença, Patrícia L. F. [UNESP]; Oliveira, Jhones L. [UNESP]; Melville, Cirano C. [UNESP]; Della Vechia, Jaqueline F. [UNESP]; De Andrade, Daniel J. [UNESP]; Fraceto, Leonardo F. [UNESP] (Springer Nature, 2018)
This Article contains an error in the order of the Figures. Figures 1, 2, 3, 4 and 5 were published as Figures 2, 3, 4, 5 and 1 respectively. The correct Figures 1, 2, 3, 4 and 5 appear below. The Figure legends are correct. (Figure Presented).